Understanding future adopters of advanced manufacturing technology: Evidences from Malaysian SMEs - Abd Rahman, Azmawani; Sambasivan, Murali; Shahron, Syairah Aimi (2010)
Advanced manufacturing technology is a computer-based technology or can simply be any technology which is advanced to a firm when compared to its previous or current manufacturing technology. These technologies include technologies that can be used to support designing, processing, packaging, and supply chain activities. This research investigates why firms do not adopt AMT although they have the intention to adopt (we term them as the “future adopters”). This paper highlights what future adopters perceive as benefits of AMT adoption. As they have the intention to adopt, but yet to adopt, the paper also unveils their major obstacles towards the technology adoption. Based on survey results of 140 SMEs, the study found that finance and lack of knowledge as the top two obstacles of AMT adoption. Further statistical analysis indicates, these hold true for both performing and less performing SMEs. Meanwhile, competitive benefits were found as a major driver for their intention to have the technology. This study contributes in terms of understanding the underlying dimensions of perceived benefits and obstacles of technology adoption within the context of the future adopters. Perhaps, a new perspective from which many more studies could be developed. The results of the study can serve as guidelines to the practitioner and the policy makers.